Positioning Airbnb and Fairbnb in the sharing-exchange continuum - Petruzzi, M.; Sheppard, V.; Marques, C. (Current Issues in Tourism, 2022)
Many organizations are positioning themselves as part of the sharing economy due to positive connotations associated with the sharing concept. Recognizing that many of these organizations represent the sharing economy to varying degrees, this study selected two organizations – Airbnb and Fairbnb, to analyze the extent to which they serve as examples of the sharing economy. A content analysis was undertaken to identify the position of each organization on a continuum, ranging from pure sharing to pure exchange characteristics. The analysis reveals that overall Fairbnb may be a stronger example of the sharing economy than Airbnb.